Efficacy and safety of twice‐ vs once‐daily dosing of lisinopril for hypertension. Issue 9 (25th April 2017) - Tsai, Tiffany; Kroehl, Miranda E.; Smith, Steven M.; Thompson, Angela M.; Dai, Isabella Y.; Trinkley, Katy E.
Abstract : This retrospective cohort study compared administration of lisinopril twice daily and once daily for hypertension. Data were collected from an ambulatory electronic health record between 2011 and 2014. Patients previously receiving lisinopril 20 mg were placed into the once‐daily cohort if changed to 40 mg once daily or into the twice‐daily cohort if changed to 20 mg twice daily. Efficacy outcome measures were change in systolic blood pressure and diastolic blood pressure and achievement of blood pressure control (<140/90 mm Hg). Of 90 patients included (45 per cohort), the mean age was 61.8 years and 17.8% were black. Once‐ and twice‐daily administrations were associated with blood pressure reductions of 6.2/1.5 mm Hg and 16.5/5.9 mm Hg, with a 10.2/4.3 mm Hg greater reduction with twice‐daily administration (systolic blood pressure, P =.016; diastolic blood pressure, P =.068). Twice‐daily lisinopril dosing was associated with greater systolic blood pressure reductions compared with the same total daily dose administered once daily.